Effects of an undoped-InGaN waveguide on the optical confinement and carrier dynamics of InGaN laser diodes. (3rd October 2018) - Paliwal, Avinash; Singh, Kuldip; Mathew, Manish
Abstract: In this paper, we have analyzed the performance of laser diodes (LDs) with an undoped In x Ga1− x N waveguide in association with variable In mole fractions varying from 0% to 6%. The InGaN waveguide significantly affected optical confinement and carrier dynamics in the LD. Laser output power, internal quantum efficiency (IQE), quantum well (QW) gain and optical confinement factor (OCF) are analyzed in correlation with In content in the waveguide. The OCF for TE1 mode at x   =  0 is 0.0079, and it increases with x . The OCF for x   =  0.06 is 0.0109. Quantum states in the QW reduced with In content, which reduced QW gain. However, improved OCF consequently improved the overall gain of the device. Peak IQE for x   =  0 is ~0.28, which increased to ~0.683 for x   =  0.06. Laser output power, slope efficiency and IQE improved with increasing In content. The threshold current density for x   =  0 is 3.911 kA cm −2, which drops to 1.806 kA cm −2 for x   =  0.06. Auger recombination, Shockley-Read-Hall recombination and electron leakage are reduced for high In content in the waveguide. Auger carrier loss remains nearly constant above the threshold, hence efficiency droop above the threshold current density is attributed primarily to leakage current density. The efficiency droop for x   =  0 is 25.59%, which increased to 36.66% for x   =  0.06 at 25 kA cm −2 current density. However, the IQE for x   =  0 at 25 kA cm −2 is 0.202, which increased to 0.436 for x   =  0.06 at 25 kA cm −2 . Slope efficiency increases with In content; slope efficiency for x   =  0.06 improves by 0.2126 W A −1 . Laser output power is improved by 1.91 W at 25 kA cm −2 for x   =  0.06.